Axitinib exposure triggers endothelial cells senescence through ROS accumulation and ATM activation - Mongiardi, Maria Patrizia; Radice, Giulia; Piras, Maurizia; Stagni, Venturina; Pacioni, Simone; Re, Agnese; Putti, Sabrina; Ferrè, Fabrizio; Farsetti, Antonella; Pallini, Roberto; Barilà, Daniela; Levi, Andrea; et al. (Oncogene, 2019)
Inhibitors of Vascular Endothelial Growth Factor target both tumor vasculature and cancer cells that have hijacked VEGF Receptors (VEGFRs) signaling for tumor growth-promoting activities. It is important to get precise insight in the specificity of cell responses to these antiangiogenic drugs to maximize their efficiency and minimize off-target systemic toxicity. Here we report that Axitinib, an inhibitor of VEGFRs currently in use as a second line treatment for advanced renal cell carcinoma, promotes senescence of human endothelial cells in vitro. A one-hour pulse of Axitinib is sufficient for triggering cell senescence. Mechanistically, this requires oxidative stress-dependent activation of the Ataxia Telangiectasia Mutated (ATM) kinase. Axitinib-mediated senescence promoting action is prevented by short-term treatment with antioxidants or ATM inhibitors, which conversely fail to prevent senescence induced by the DNA-damaging drug doxorubicin. Coherently, induction of oxidative stress-related genes distinguishes the response of endothelial cells to Axitinib from that to doxorubicin. Importantly, an Axitinib pulse causes cell senescence in glioblastoma cells. However, neither antioxidants nor ATM inhibitors can reverse this phenotype. Thus, antioxidants may selectively protect endothelial cells from Axitinib by decreasing systemic toxicity and maintaining a functional vascularization necessary for efficient delivery of chemotherapeutic drugs within the tumor mass.